Marginal people in deviant places : ethnography, difference, and the challenge to scientific racism - Irvine, Janice M. (University of Michigan Press, 2022)
Marginal People in Deviant Places revisits twentieth-century ethnographic studies of deviance, arguing that ethnographies that focus on marginal subcultures--ranging from Los Angeles hoboes to men who have sex with other men in St. Louis bathrooms, to taxi dancers in Chicago, to elderly Jews in Venice, California--produce new ways of thinking about social difference more broadly in the United States. Irvine demonstrates how the social scientists who told the stories of these marginalized groups offered an early challenge to then-dominant narratives of scientific racism and then offers a social history of certain American outsiders and a prehistory of the academic fields of ethnic studies and sexuality studies. Through the stories Irvine recounts in this book, she identifies an American paradox represented in a simultaneous desire for and rejection of outsiders and describes the rise of an outsider capitalism that integrates difference into American society by marketing it. Place plays a crucial role in this work as Irvine examines its role in shaping ethnographies about outsiders and therefore understandings of social difference. Irvine has visited the sites of each of the ethnographies about which she writes, collecting photos, videos, and archival materials that will help readers understand the importance of place in the generation of particular ethnographic stories. The open-access online edition of this book is richly illustrated to help convey the deep sense of emplacement of the ethnographies discussed in this book and includes a series of interviews with sociologists about how they conduct their work and understand their forebears.